Clinical spectrum of male patients with OFD1 mutations - Sakakibara, Nana; Morisada, Naoya; Nozu, Kandai; Nagatani, Koji; Ohta, Toshiyuki; Shimizu, Junya; Wada, Takuzo; Shima, Yuko; Yamamura, Tomohiko; Minamikawa, Shogo; Fujimura, Junya; Horinouchi, Tomoko; et al. (Journal of human genetics, 2019)
Oral-facial-digital syndrome type 1 (OFD1) is a ciliopathy characterized by oral, facial, and digital malformations that are often accompanied by polycystic lesion of the kidney and central nervous involvement. OFD1 shows an X-linked recessive inheritance caused by mutation in the OFD1 gene (Xp22.2). The disease is generally considered embryonic lethal for hemizygous males. However, males with OFD1 mutations were recently reported. Here, we report four additional Japanese male patients with OFD1 variants and describe the variable clinical manifestation and disease severity among the four patients. Patient 1 with pathogenic indels including a 19-bp deletion and 4-bp insertion (c.2600-18_2600delinsACCT) had end-stage renal disease (ESRD) with bilateral cystic kidneys and sensory hearing loss. He showed neither intellectual disability nor facial or digital dysmorphism. Patient 2 with a missense variant in exon 7 (c.539 A > T, p.Asp180Val) presented head circumference enlargement, brachydactyly, high-arched palate, micropenis, severe global developmental delay, and ESRD. Patient 3 had a single base substitution at the splice donor site of intron 16 (c.2260 + 2 T > G) causing a 513-bp deletion at the transcript level. The patient had chronic kidney disease and speech delay, but no oral, facial, or digital dysmorphism. His uncle (patient 4) carried the same OFD1 variant and showed ESRD with extra-renal malformations including obesity and micropenis, which was previously diagnosed as Bardet-Biedl syndrome. The OFD1 mutations were not lethal in these four male patients, likely because the three mutations were in-frame or missense. This report provided insights into the onset mechanism and phenotype-genotype association in patients with OFD1 mutations.